The influence of service quality and product innovation on purchasing decisions of Seblak Mama Radit Cimone-Tangerang - Delia Apriyani; Suryanto Sosrowidigdo; Diah Pitaloka Setiawati; Eva Triana Dewi (Junal Ilmu Manajemen, 2023)
In today's increasingly fierce business environment, manufacturers must constantly use their creativity and critical thinking skills to expand their businesses. This investigation attempts to learn: the impact of customer service standards on mom radit Cimone-Tangerang's purchase choices. The impact of product innovation on Seblak mama's Cimone-Tangerang purchase choice. In this study, saturated sampling—a type of non-probality sampling—was employed as the sample method. Consumers who visit Mama Radit Cimone-Tangerang seblak stand with the intention of purchasing products from that stall make up the population of this study. There were 100 respondents in the research sample. Multiple linear regression is the data analysis method employed in this study, along with correlation testing, determination testing using R Square (R2), and other techniques. To clarify how research on hypotheses utilizing such analysis is described. The findings of the data analysis demonstrate: When the purchasing decision variable has not been modified by other variables, especially service quality variables (X1) and product innovation variables (X2), the value of 3.625 is a constant or state. The purchase decision variable remains unchanged if the independent variable is absent. According to the regression coefficient X1 value, b1, which is 0.262, service quality variables positively influence purchasing decisions. This means that, assuming no other variables are taken into consideration in this study, every increase of 1 unit in service quality variables will have an impact on purchasing decisions by 0.262. With a b2 (value of regression coefficient X2) of 0.568, the product innovation variable is shown to positively affect purchasing decisions. This means that, assuming no other variables are taken into consideration in this study, every unit increase in the product innovation variable will increase the impact of purchasing decisions by 0.568.